FORMULASI DAN EVALUASI FISIK SEDIAAN GEL DAUN PEGAGAN (Centella Asiatica) SEBAGAI ANTI JERAWAT - Sabiti, Farroh Bintang; Perwitasari, Yustina Intan (Jurnal Farmasi & Sains Indonesia, 2024)
Currently, many topical anti-acne drugs are circulating in the form of gels and creams, but there arestill very few topical anti-acne drugs that contain herbs, as active ingredients or agents that canpotentially prevent and treat acne, such as gotu kola (Centella asiatica) with its anti-bacterialproperties. The aim of this research is to develop a stable gotu kola gel formulation. The method used isexperimental research methodology. Based on the research results, 1 optimum formula was obtained,namely formulas 1 and 2 with colors following the color of the active substance and transparent, havinga distinctive, homogeneous odor, pH 4.5-6.5, good spreadability (5-7 cm) and viscosity ( 3,000-50,000cP).